An investigation of the interactions between psychosocial risk factors and their health impact: mechanisms and consequences. (17th May 2019) - Abaeian, Hossein; Al-Hussein, Mohamed; Moselhi, Osama
Despite the increase in research on psychosocial hazards, studies are unable to evaluate the inter-relationships among psychosocial risk factors (PRFs) from a risk network perspective, and their findings are usually limited to bivariate relationships between PRFs and their adverse outcomes. Also, they are unable to draw the pathways by which PRFs can affect workers' health leading to impaired job performance. The present study performs a comprehensive literature review on the psychosocial risk-related research and provides an evidence-based list for major PRFs. In addition, social network analysis (SNA) is implemented for developing the psychosocial risk network for further evaluation of the interactions between variables leading to the identification of key PRFs that play important roles in structuring the entire risk network. In the next step, a system dynamic (SD) model is developed to provide the mechanism underlying the development of musculoskeletal disorders and productivity loss due to exposure to psychosocial stressors.